PENGARUH KONTEN FOOD VLOGGER, PROMOSI INSTAGRAM, DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BAKPIA JUWARA SATOE SOLO - Yuliana, Enny; Handaruwati, Indah (LPPM UNISDA, 2025)
The increasingly developing times make technology also more advanced, especially Instagram social media which has been widely used by the general public to post photos, make videos (vlogs), and do promotions on Instagram. This study aims to provide empirical evidence of the influence of food vlogger content, Instagram promotion, and product innovation on the purchase decision of Bakpia Juwara Satoe Solo products. The sample used in this study was 40 people. Sample determination by purposive sampling method. The results of this study show that food vlogger content does not have a significant effect on the purchase decision of Bakpia Juwara Satoe Solo products, Instagram promotion has a significant effect on the purchase decision of Bakpia Juwara Satoe Solo products, product innovation has a significant effect on the purchase decision of Bakpia Juwara Satoe Solo products.